Fluoromethyl phenyl sulfoxide: Highly convenient syntheses of vinyl fluorides and fluoromethylketones - Vichai Reutrakul (2018)
Alkylation of lithio fluoromethyl phenyl sulfoxide 2 gave the alkylated products in high yields. Pyrolysis of the products led to vinyl fluorides in excellent yields. The reaction of 2 with carbonyl compounds led to the corresponding β-hydroxy-α-fluoromethyl phenyl sulfoxides. Pyrolysis of some of the sulfoxides gave fluoromethylketones in moderate yields. © 1983.